Comparative estimation of regulatory systems’ functional state of regularly exercising and not exercising sports students - Konkabaeva, A.E.; Baranova, T.I.; Tykezhanova, G.M.; Nurlybaeva, K.A.; Кanafina B.A.; Bugembaeva, A.T.; Rasol, M. (Fundamental and Experimental Biology, 2015)
The article presents the results of survey of two groups of male students (mean age 20 ± 2) from the Department of Physical Culture and Sports as well as the biology and geography departments. The heart rate variability was examined using a computerized complex «Varikard» (Russia). Estimation of heart rate variability was performed using mathematical statistics method of R.M.Baevsky. Cardiovascular system’s fitness was estimated by determining the type of response to the diving reflex using the method of cold-hypoxia-hypercanic effect (CHE). There was a substantial stress and strain of regulatory systems at the majority of students of the Faculty of Physical Education and Sport, what shows a decline of adaptive reserves of the body, caused by excessive loads.